CRT combined with a sequential VMAT boost in the treatment of upper thoracic esophageal cancer. (6th September 2013) - Jin, Xiance; Yi, Jinling; Zhou, Yongqiang; Yan, Huawei; Han, Ce; Xie, Congying
Abstract : The purpose of this study is to investigate the potential benefits of conformal radiotherapy (CRT) combined with a sequential volumetric‐modulated arc therapy (VMAT) boost in the treatment of upper thoracic esophageal cancer. Ten patients with upper thoracic esophageal cancer previously treated with CRT plus a sequential VMAT boost plan were replanned with CRT plus an off‐cord CRT boost plan and a full course of VMAT plan. Dosimetric parameters were compared. Results indicated that CRT plus off‐cord CRT boost was inferior in planning target volume (PTV) coverage, as indicated by the volume covered by 93% ( p = 0.05 ) and 95% ( p = 0.02 ) of the prescription dose. The full course VMAT plan was superior in conformal index (CI) and conformation number (CN), and produced the highest protection for the spinal cord. CRT plus a VMAT boost demonstrated significant advantages in decreasing the volume of the lung irradiated by a dose of 10 Gy ( V 10, p = 0.007 ), 13 Gy ( V 13, p = 0.003 ), and 20 Gy ( V 20, p = 0.001 ) . The full course VMAT plan demonstrated the lowest volume of lung receiving a dose of 30 Gy. CRT plus a VMAT boost for upper thoracic esophageal cancer can improve the target coverage and reduce the volume of lung irradiated by an intermediate dose. This combination may be a promising treatment technique for patients with upper thoracic esophageal cancer. PACS number: 87.53.Kn, 87.55.x, 87.55.D, 87.55.dk